Atherosclerosis Immunoimaging by Positron Emission Tomography. Issue 4 (April 2020) - Pérez-Medina, Carlos; Fayad, Zahi A.; Mulder, Willem J.M.
Abstract : The immune system's role in atherosclerosis has long been an important research topic and is increasingly investigated for therapeutic and diagnostic purposes. Therefore, noninvasive imaging of hematopoietic organs and immune cells will undoubtedly improve atherosclerosis phenotyping and serve as a monitoring method for immunotherapeutic treatments. Among the available imaging techniques, positron emission tomography's unique features make it an ideal tool to quantitatively image the immune response in the context of atherosclerosis and afford reliable readouts to guide medical interventions in cardiovascular disease. Here, we summarize the state of the art in the field of atherosclerosis positron emission tomography immunoimaging and provide an outlook on current and future applications.